Cross-Cultural Comparison of How Mind-Body Practice Affects Emotional Intelligence, Cognitive Well-Being, and Mental Well-Being - Walter, Ofra; Shenaar-Golan, Vered; Routray, Surekha (Frontiers in Psychology, 2021)
The study tested cross-cultural differences of Israeli and Indian participants in the outcomes of mind-body practice (MBP) on emotional intelligence (EI), cognitive well-being, and mental well-being, as well as the predictive role of gender and MBP on cognitive and mental well-being. It drew on a sample of 699 Indian and Israeli participants (ages 18‒65) from urban settings. Questionnaires were used to measure cognitive well-being, demographics, EI, and mental well-being. EI was assessed using the Self Report Emotional Intelligence (SREIT); cognitive well-being was assessed using the Personal Well-being Index; mental well-being was assessed using the Warwick-Edinburgh Mental Well-being Scale (WEMWBS). The effect of the demographic parameters was tested using the two-sample T-test or the Chi-square test. The associations between EI, mental, and cognitive subscales were evaluated using the Pearson correlation coefficient and linear regression with stepwise selection. Results indicated MBP affected EI in both cultures but Indian participants showed higher EI, while Israeli participants showed lower EI. Israelis also reported higher mental well-being. Future research should examine EI as ability (we examined it as a trait) thus contributing to a better understanding of the similarities and differences between trait and ability EI in different cultures. Future work should also probe gender differences.